Feminist thought a more comprehensive introduction - Tong, Rosemarie 1947-; Botts, Tina Fernandes (Routledge, 2018)
A classic resource on feminist theory, Feminist Thought offers a clear, comprehensive, and incisive introduction to the major traditions of feminist theory, from liberal feminism, radical feminism, and Marxist and socialist feminism to care-focused feminism, psychoanalytic feminism, and ecofeminism. The fifth edition has been thoroughly revised, and now includes a new chapter on Third Wave and Third Space Feminism. Also added to this edition are significantly expanded discussions on women of color feminisms, psychoanalytic and care feminisms, as well as new examinations of queer theory, LGBTQ and trans feminism
Keywords: Feminist theory